THE FORMATION OF MASS CULTURE AND ITS EFFECTS ON CONTEMPORARY ART - Serpil YAYMAN ATASEVEN (Fırat University, 2019)
Mass culture appeared as part of the changes capitalism brought about on the society. Mass culture, appearing in the 19th century as a result of growing effect of capitalism and developments in advertising, is also called popular culture. This trend changed people’s lifestyle as well as their approach to art, prompting people to overconsume and turning works of art into ordinary commodities. Therefore, the capitalist system created a cultural life and art market based on money, ensuring the continuity of consumption. Mass society came into being with people having similar points of view and exhibiting analogous behaviour. These changes in the realms of culture and art have been investigated by artists, authors, and scholars who critically examined their causes and effects. The first critical approach to the phenomenon of mass culture was that of Theodor Adorno in the 1930s. Adorno maintained that the efforts to settle the differences between modernist high art and industrial mass culture caused the disappearance of high art, and asserted that changes in social life commodified works of art. In his paintings, Andy Warhol, the pioneer of Pop Art, depicted the commodified works of art becoming mechanical and ordinary. What influenced art negatively in mass culture was, according to Warhol, mass produced “kitsch”. The studies by the Frankfurt school on this issue have revealed the profound effect of mass media in the promotion of popular culture, claiming that mass media serve global market and its ideology, leading to uniform production of works of art. This study aims to investigate the negative implications of mass culture and the changes it has caused in the realm of art. Critics of mass culture commonly argue that it causes people to adopt a consumption-focused approach which is indifferent, passive, and away from traditional values.